ESTIMATION OF SOLUBILITY PARAMETERS OF POLY(METHYL METHACRYLATE) AND DERIVATIVES BY INVERSE GAS-CHROMATOGRAPHY - KAYA, I; OZDEMIR, E (Marcel Dekker Inc, 1995)
Flory - Huggins polymer-solute interaction (chi(12)) parameters have been determined by inverse gas chromatography (i.g.c.) at 453-463 K for alkanes, alcohol,acetates, ketones and O - Xylene in PMMA. PEMA, PIBMA and Pt-BMA to estimate the polymer solubility parameters (delta(2)) Partial molar free energies of mixing (Delta G(1)(infinity) ) and weight fraction activity coefficients of solute probes at infinite dilution (Omega 1(infinity) ) were calculated at temperature range 453-463 K.